(untitled) (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To compare the method of surface anatomical landmark with the method of pre-procedural ultrasonography assisted midline approach for identification of inter-spinous lumber level for spinal anesthesia in elective cesarean section cases. STUDY DESIGN: Randomized Control Trial STUDY SETTING: Obstetric floor, department of anesthesia, Hayatabad Medical Complex Peshawar DURATION OF STUDY: 6 months SUBJECT AND METHODS: All the patients due for elective C-sections under spinal anesthesia were enrolled in the study keeping in view the inclusion/ exclusion criteria. A written informed consent were obtained from all the enrolled patients. All the enrolled patients were divided into two groups, Group A being Ultrasound-guided technique and Group B being surface landmark-guided technique. During the procedure, parameters such as insertion attempts, passes and time taken for performing the procedure was recorded in both the groups. All the information obtained were recorded in a proforma attached. RESULTS: This study was conducted on 68 patients presented for elective C-section. Patients were divided into two group, 34 in each group. In group A (ultrasound) group the mean age of the patients was 29.12±5.9 years and in group B (landmark) group the mean age was 27.97±6.82 years. The mean no of insertion attempts in group A was 1.24±0.61 and in group B it was 2.79±1.99. The mean no of needles passes was 2.97±1.38 in group A and in group B it was 7.71±2.70. The mean procedural time in group A was 4.26±1.18 minutes and 6.26±2.09 minutes in group B. According to age distribution, in group A 18 (52.9%) patients were in the age group of 18 to 28 years and 16 (47.1%) in the age group of 29 to 40 years. In group B 19 (55.9%) patients belonged to the age group of 18 to 28 years and 15 (44.1%) belonged to the age group of 29 to 40 years. According to the comparison of first attempt success in both groups, 85.3% success rate was observed in group A and 47.1% success rate was observed in group B, the difference was statistically significant (P-value < 0.05). CONLCUSION: From our study we conclude that preprocedural ultrasonography assisted midline approach is an effective method for identification of inter-spinous lumber level for spinal anesthesia in elective cesarean section cases as compared to the method of surface anatomical landamark. Preprocedural ultrasonography assisted midline approach had 85.3% first attempt success rate as compared to surface anatomical landmark method which had first attempt success rate of 47.1% (P-value < 0.05). The difference was statistically significant.